2021
DOI: 10.14307/jfcs113.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Managing Academic Excellence in a Crisis: Experiential Learning

Abstract: Family and consumer sciences (FCS) has a long history in embracing the value of hands-on, project-based learning in the classroom. The value of this learning style extends beyond the classroom through internships and other types of experiential learning. FCS literature is replete with examples from the early years of the profession to more recent years (e.g., Bell & Haley, 1995; Branegan & Spafford, 1949; Brooks & Simpson, 2014; Dobbs-Oates, 2019; Hurst et al., 2014; Olson & Montgomery, 2000).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed, this was the case for our program, which comprised 93 interns placed across various sites. Other students and internship programs felt the challenges as described in the results (Harden et al, 2021;Mitchell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this was the case for our program, which comprised 93 interns placed across various sites. Other students and internship programs felt the challenges as described in the results (Harden et al, 2021;Mitchell et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that issues with equity, communication, internet access will probably persist post-pandemic and that universities must prioritize equitable access and quality control as it relates to internships. Harden et al (2021) examined the impact of the pandemic on Family and Consumer Sciences programs, including hospitality, fashion design, and merchandising, and provided a review of the processes used to help students adjust to the realities of the pandemic. Students showed resilience and could adapt to the changing dynamic and get a realistic view of the challenges companies faced during the pandemic.…”
mentioning
confidence: 99%